Chronic exposure to Pb2+ perturbs ChREBP transactivation and coerces hepatic dyslipidemia. Issue 21 (27th July 2019) - Vineeth Daniel, P.; Kamthan, Mohan; Gera, Ruchi; Dogra, Surbhi; Gautam, Krishna; Ghosh, Debabrata; Mondal, Prosenjit
Abstract : Dysregulated hepatic de novo lipogenesis contributes to the pathogenesis of nonalcoholic fatty liver disease in both humans and rodents. Clinical evidence suggests fatty liver to have a positive correlation with serum lead (Pb 2+ ) levels. However, an exact mechanism of Pb 2+ ‐induced fatty liver progression is still unknown. Here, we show that exposure to Pb 2+ regulates ChREBP‐dependent hepatic lipogenesis. Presence of Pb 2+ ions within the hepatocytes reduces transcript and protein levels of sorcin, a cytosolic adaptor partner of ChREBP. Adenovirus‐mediated overexpression of sorcin in Pb 2+ exposed hepatocytes and an in vivo mouse model ameliorates liver steatosis and hepatotoxicity. Hereby, we present Pb 2+ exposure to be a lethal disruptor of lipid metabolism in hepatocytes and highlight sorcin as a novel therapeutic target against Pb 2+ ‐induced hepatic dyslipidemia. Abstract :